Case Report: A Novel Synonymous ARPC1B Gene Mutation Causes a Syndrome of Combined Immunodeficiency, Asthma, and Allergy With Significant Intrafamilial Clinical Heterogeneity - Papadatou, Ioanna; Marinakis, Nikolaos; Botsa, Evanthia; Tzanoudaki, Marianna; Kanariou, Maria; Orfanou, Irene; Kanaka-Gantenbein, Christina; Traeger-Synodinos, Joanne; Spoulou, Vana (Frontiers in Immunology, 2021)
Most recently, a novel syndrome of combined immune deficiency, allergy and inflammation has been attributed to mutations in the gene encoding ARPC1B, which is a key molecule driving the dynamics of the cytoskeleton. Homozygous mutations in the ARPC1B gene have been found to result in disruption of the protein structure and cause an autosomal recessive syndrome of combined immune deficiency, impaired T cell migration and proliferation, increased levels of immunoglobulins E & A and thrombocytopenia. Up to date, only a few individuals have been diagnosed with ARPC1B deficiency syndrome worldwide. In this case series, we report the wide spectrum of phenotype in three children of a consanguineous family from Afghanistan with a novel homozygous synonymous pathogenic variant c.783G>A, p.(Ala261Ala) of the ARBC1B gene that causes a similar syndrome, but no thrombocytopenia. Targeted RNA study demonstrated that the variant affects the splicing process of mRNA and results in partial haploinsufficiency of the gene in the affected patients, due to premature termination. The Next Generation Sequencing studies facilitated the diagnosis of this rare Combined Immunodeficiency and led to the decision to treat the affected patients with HCT from an HLA-matched healthy sibling.